Cancer patient knowledge about and behavioral intentions after germline genome sequencing. Issue 3 (March 2022) - Napier, Christine E.; Davies, Grace; Butow, Phyllis N.; Schlub, Timothy E.; Best, Megan C.; Bartley, Nicci; Juraskova, Ilona; Meiser, Bettina; Tucker, Katherine M.; Biesecker, Barbara B.; Thomas, David M.; Ballinger, Mandy L.; et al.
Highlights: Cancer patients/relatives having germline genome sequencing had moderate GS knowledge. Most participants had high intentions to change behavior if at high risk of cancer. Men and those from low socio-economic background had less behavior change intentions. Low self-efficacy and high uncertainty tolerance is associated with lower intentions. Those with low intention to change behavior may need support to aid behavior change. Abstract: Objectives: Germline genome sequencing (GS) is becoming mainstream in cancer diagnosis and risk management. Identifying knowledge gaps and determinants of health behavior change intentions will enable effective targeting of educational and management strategies to translate genomic findings into improved cancer outcomes. Methods: Probands diagnosed with cancer of likely genetic origin that consented to but not yet undergone GS, and their biological relatives, completed a cross-sectional questionnaire assessing GS knowledge and hypothetical intention to change behaviors. Results: Probands (n = 348; 57% university educated) and relatives (n = 213; 38% university educated) had moderate GS knowledge levels, with greater knowledge associated with higher education. Both populations reported high behavioral change intentions, significantly associated with being female (p = 0.01) and greater perceived importance of GS (p < 0.001), and for probands: being from English-speaking households (p = 0.003), higher socio-economic status (p = 0.01) and greater self-efficacy (p = 0.02). Conclusions: Increasing GS knowledge will enable realistic participant expectations surrounding germline GS. Actual behavior change should be monitored to determine whether increased cancer risk knowledge results in altered cancer-related behavior and ultimately, cancer outcomes. Practice implications: Educational resources should target specific populations to ensure informed decision-making and expectation management. Support tools facilitating and maintaining behavioral change may be needed to achieve improved cancer patient outcomes.